Attenuating effect of vigorous physical activity on the risk for inherited obesity: a study of 47,691 runners. - Paul T Williams (Public Library of Science (PLoS), 2012)
Objective Physical activity has been shown to attenuate the effect of the FTO polymorphism on body weight, and the heritability of body weight in twin and in family studies. The dose-response relationship between activity and the risk for inherited obesity is not well known, particularly for higher doses of vigorous exercise. Such information is needed to best prescribe an exercise dose for obesity prevention in those at risk due to their family history. Design We therefore analyzed self-reported usual running distance, body mass index (BMI), waist circumference, and mother's and father's adiposity (1 = lean, 2 = normal, 3 = overweight, and 4 = very overweight) from survey data collected on 33,480 male and 14,211 female runners. Age-, education-, and alcohol-adjusted regression analyses were used to estimate the contribution of parental adiposities to the BMI and waist circumferences in runners who ran an average of <3, 3-6, 6-9, ≥ 9 km/day. Results BMI and waist circumferences of runners who ran <3 km/day were significantly related to their parents adiposity (P<10(-15) and P<10(-11), respectively). These relationships (i.e., kg/m(2) or cm per increment in parental adiposity) diminished significantly with increasing running distance for both BMI (inheritance×exercise interaction, males: P<10(-10); females: P<10(-5)) and waist circumference (inheritance × exercise interaction, males: P<10(-9); females: P = 0.004). Compared to <3 km/day, the parental contribution to runners who averaged ≥ 9 km/day was diminished by 48% for male BMI, 58% for female BMI, 55% for male waist circumference, and 58% for female waist circumference. These results could not be attributed to self-selection. Conclusions Exceeding the minimum exercise dose currently recommended for general health benefits (energy equivalent to running 2-3 km/day) may substantially diminish the risk for inherited obesity. The results are consistent with other research suggesting the physical activity dose required to prevent unhealthy weight gain is greater than that recommended for other health benefits.